Pengaruh Kualitas Pelayanan, Persepsi Harga, dan Kualitas Produk terhadap Keputusan Pembelian di Sushimas Depok - Shafitri, Tiara Nur; Paludi, Salman (Indonesian Journal Publisher, 2024)
The purpose of this research is to determine the influence of service quality, price perceptions and product quality on purchasing decisions at Sushimas Depok. Data was obtained from questions distributed in the form of a questionnaire via the Google Form link (primary data). The sampling technique used was Accidental Sampling of 100 respondents. Data was collected through questionnaires and analyzed using the multiple linear regression method with the help of SPSS 25 software. The research results prove that service quality has no significant effect on purchasing decisions, price perception has no significant effect on purchasing decisions, and product quality has a significant effect on purchasing decisions. This shows that consumers really appreciate the high quality and consistency of the products offered, thereby increasing their trust and loyalty to the Sushimas brand. Simultaneously, the variables of service quality, price perception and product quality have a positive and significant effect on purchasing decisions at Sushimas Depok.